Presenting findings on subjects' behaviours: a genre-based study of linguistic and educational research reports - Lim, Jason Miin Hwa (2007)
While different categories of findings are frequently presented in linguistic and educational research papers, four categories of results are closely associated with descriptions of groups’ and individuals’ behaviours respectively. These categories deserve much attention in an ESP course for students in the related disciplines as numerous studies involve detailed descriptions of subjects’ behaviours. Understandably, undergraduate and postgraduate students are expected to describe subjects’ behaviours in appropriate and comprehensible ways that are generally accepted by members of the academic discourse community, particularly examiners of research reports and dissertations. Using a qualitative genre analysis of two corpora of Results sections in linguistic and educational research articles published from 2002 to 2004, the researcher has studied the various patterns in which behaviours of subjects are presented as findings. Given that numerous linguistic problems are often encountered by novice writers while attempting to present findings in English research reports, this paper discusses the relevant linguistic resources that ESP instructors need to highlight in the process of teaching second language learners how to present findings pertaining to the descriptions of behaviours. The findings of this study have important pedagogical implications for developing language literacy as they distinctly show how concepts of rhetorical categories and their associated linguistic choices can be effectively applied in teaching tertiary students to describe subjects’ behaviours in an interesting range of research contexts.